Geografia econômica da implantação da usina hidrelétrica Governador Ney Aminthas de Barros Braga (Segredo) - PR - Zwaricz, Juliano (2013)
The energy issue in Brazil and Paraná, especially the electric power sector, has been the subject of much discussions and debates, whether in the academic, political or economic, as backdrop for "development" of a region. It is in this bias that sought the understanding about this topic for the production of this dissertation, with emphasis on the construction of hydroelectric power plants, economic development of Paraná and consequently of region of South-Central, where it was built an energy complex, including the Secret Power Plant, today Governor Ney Braga. However, it was necessary to conceptualize region; region for the electricity sector; territory; territorialization-deterritorialization-reterritorialization-TDR; and to analyze the relationships between large investment projects, nature and sustainability for to give theoretical support to empiricism present in the interviews of the riversides, traders, mayor, aldermen, state and federal deputies, all these involved in the implementation process of Hydroelectric Governor Ney Braga. Therefore, we could raise the process of the Economic Geography of Cantuquiriguaçu Association in the Mid-South Paranaense, specifically in the municipalities of Candói, Foz do Jordão, Pinhão, Reserva do Iguaçu, Mangueirinha, Honório Serpa and Coronel Domingos Soares, who emancipated themselves after the construction of the Hydroelectric Governor Ney Braga. Besides the implementation of resettlement Secret I, II, III and IV for to reterritorializar the riversides hit by the lake. We could discuss yet, the process here called the legal war between the winner contractor of the bid and Copel, locked in the courts of justice, as well as the current situation of the resettlement and of the agriculture projects deployed for riversides. We finished the survey finding that the economic impact, social and environmental it was higher than the predicted in the EIA-RIMA drafted in 1987.